Analisis Kemampuan Berpikir Kreatif Matematis Ditinjau Dari Tingkat Resiliensi Matematis Siswa SMP Negeri 1 Batang Kuis - Erny Silaban; Dame Ifa Sihombing; Golda Novatrasio Sauduran (Jurnal Pendidikan Dasar Islam, 2024)
The aim of this study is to determine if mathematical resilience and capacity for creative thought are related among eighth-grade mathematics students at SMP Negeri 1 Batang Kuis. This study employs a quantitative research design with a descriptive technique to gather data on students' proficiency in solving mathematical problems using rectangular flat materials. The study's population comprises all grade VIII students at SMP Negeri 1 Batang Kuis, which consists of 10 classes. From this population, a sample of 30 students from class VIII-7 was selected and categorized into three levels of mathematical resilience: high, medium, and low. The mathematical creative thinking skills of these 30 students were subsequently analyzed to explore the relationship between mathematical resilience and creative thinking abilities using specific instruments. The instruments employed include the Mathematical Resilience Test and the Mathematical Creativity Test. The analysis of mathematical creative thinking skills is based on four indicators: (1) fluency of thinking, (2) flexibility of thinking, (3) originality of thinking, and (4) elaboration ability. The results from the simple regression analysis yielded the regression equation \(Y = 0.387 + 0.3867X\). In this equation, the coefficient for X is positive, indicating a positive linear relationship between the two variables. Additionally, the calculation of the simple correlation coefficient resulted in \(R_{cal} = 0.528\), which suggests a moderate correlation. This indicates that the ability to think creatively in mathematics is influenced by 27.9% of the mathematical resilience among Grade VIII students when solving problems related to rectangular flat shapes